ANALISIS KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Kanivia, Aan; Dewi, Isti Riana; Rahmawati, Dewi; Wibowo, Kimiko Alberta (Politeknik Negeri Ambon, 2023)
This study aims to analyze the impact of financial ratios on stock returns in LQ 45 companies listed on the Indonesia Stock Exchange. The four financial ratios examined are Return on Equity (ROE), Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO). Data were obtained from the financial statements of companies listed on the IDX during the period 2020-2022. The analysis method used was multiple linear regression. The results of the study show that Debt to Equity Ratio (DER) has a negative and significant impact on stock returns, while Return on Equity (ROE) has a positive and significant impact on stock returns. However, Total Asset Turnover (TATO) does not have a significant impact on stock returns. The simultaneous test results indicate that all four independent variables (CR, DER, ROE, and TATO) collectively have a significant impact on stock returns. This research provides theoretical benefits for academics in expanding their understanding of the impact of financial ratios on stock returns. Additionally, the findings of this study have practical implications for companies, investors, and prospective investors in making investment decisions in the capital market.